From social science to data science - Hogan, Bernie (Los Angeles SAGE, 2023)
From Social Science to Data Science is a fundamental guide to scaling up and advancing your programming skills in Python. From beginning to end, this book will enable you to understand merging, accessing, cleaning and interpreting data whilst gaining a deeper understanding into computational techniques and seeing the bigger picture. With key features such as tables, figures, step-by-step instruction and explanations giving a wider context, Hogan presents a clear and concise analysis on key data collection and skills in Python. --
Part I: Thinking Pragmatically--Chapter 1. Introduction --Chapter 2. The Series --Chapter 3. The DataFrame --Part II: Accessing and Converting Data--Chapter 4. File Types --Chapter 5. Merging and Grouping Data --Chapter 6. Accessing the Web --Chapter 7. Accessing APIs --Part III. Interpreting Data: Expectations versus Observations--Chapter 8. Research Questions --Chapter 9. Visualising Expectations --Part IV: Social Data Science in Practice: Four Approaches--Chapter 10. Cleaning Data --Chapter 11. Introducing Natural Language Processing --Chapter 12. Introducing Time Series Data --Chapter 13. Introducing Network Analysis --Chapter 14. Introducing Geographic Information Systems --Chapter 15. Conclusion
Includes bibliographical references and index.
Keywords: Data mining; Python (Computer program language); Python (Computer program language); Social sciences -- Research -- Data processing; Social sciences -- Research -- Data processing